Biochemical compounds and sub-chronic toxicity test of Chlorella sp. and Spirulina sp. isolated from Glagah Coastal Water - Slamet Widiyanto; Mulyati Sarto; Laksmindra Fitria; Rahadian Yudo; Eko Agus Suyono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Microalgae are microscopic photosynthetic organisms found in marine and freshwater environments. This organism is a eukaryotic group of polyphyletic and very diverse. This study investigated the biochemical composition and sub-chronic test of Chlorella Sp. and Spirulina Sp. isolated from Glagah coastal water (Yogyakarta, Indonesia) as a preclinical study to create potential nutritional supplement for human health. Microalgae culture was analyzed for biochemical composition using several methods: AAS for metal analysis (Pb, Cu, Fe, Mg, Zn, and Hg), GC-MS and UV spectrophotometer for fatty acid profiles analysis (lenolenic acid, eicosatrienoic acid, arachidonic acid, linoleic acid, oleic acid, eicosenoic acid, EPA, DHA, omega 6 and 9), Alkaloids, Steroids, Tanin and Saponin. The next step is to do a sub-chronic test of microalgae biomass using experimental animals. The result shows that Spirulina sp. and Chlorella sp. contain 16 and 10 different biochemical compounds respectively. Furthermore, organic nutritional properties in both of microalgae are relatively high with a rich biochemical profile of Fe and nutritious poly-unsaturated fats (such as linolenic acid, arachidonic acid , omega 6, and 9). Regarding sub-chronic toxicity test, it was clear that Spirulina and Chlorella did not affect the blood profile. These findings suggest that both of Glagah strain microalgae are considered to have great potential as a multi-nutritional human health supplement.